Peningkatan Penggunaan Teknologi Informasi dalam Edukasi Pemasaran Digital Pelaku Usaha Rumahan - Abulwafa Muhammmad; Dhio Saputra (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
Home-based business actors are one of the many business fields that play a role in supporting the economy in Indonesia. Home business actors are part of MSMEs (Micro, Small and Medium Enterprises) which must always keep abreast of existing changes and developments. One of the changes and developments that have a major influence in the field of home business marketing is Information Technology. This is a challenge for home businesses to always learn to increase the use of information technology with digital marketing - social media (wa, instagram, facebook), and understand the concept of digital business well. Digital marketing requires home businesses to have good product photo and product branding skills. The existence of community service activities that provide learning about digital marketing and increasing the use of information technology can improve the skills and insights of home-based business actors to continue to struggle in digital marketing.